2018
DOI: 10.1088/1361-6528/aad111
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hesperetin-loaded PLGA nanoparticles by two different experimental design methods and biological evaluation of optimized nanoparticles

Abstract: Hesperetin was effectively encapsulated into poly (d,l-lactic-co-glycolic acid) nanoparticles by using experimental design methods. A seven-factor Plackett-Burman design was used in order to determine the major process parameters. A significant linear equation, which shows the effect of each process parameter on encapsulation efficiency was developed, and then the most effective factors were determined. Further investigation and optimization was carried out by applying the three-factor three-level Box-Behnken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…On the other hand, incubation with HspNPs for 24 and 48 h resulted in dose and time dependent decrease in cell viability, with IC 50 of 28 and 21 lg/mL, respectively. In contrast, it has been recently reported that Hsp and HspNPs have showed very low inhibition effect on cell viability of L929 fibroblast cells, which indicates they did not show any significant cytotoxicity to normal cells [23]. At the same concentration, HspNPs drastically decreased cell viability compared to free Hsp.…”
Section: Dose-and Time-dependent Cytotoxic Effect Of Hsp and Hspnps Omentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, incubation with HspNPs for 24 and 48 h resulted in dose and time dependent decrease in cell viability, with IC 50 of 28 and 21 lg/mL, respectively. In contrast, it has been recently reported that Hsp and HspNPs have showed very low inhibition effect on cell viability of L929 fibroblast cells, which indicates they did not show any significant cytotoxicity to normal cells [23]. At the same concentration, HspNPs drastically decreased cell viability compared to free Hsp.…”
Section: Dose-and Time-dependent Cytotoxic Effect Of Hsp and Hspnps Omentioning
confidence: 75%
“…HspNPs were prepared by a modified oil in water (o/w) single emulsion solvent evaporation method described as in our previous study [23]. According to this method, the organic phases consisted of PLGA and hesperetin were dissolved into DCM and acetone, respectively.…”
Section: Nanoparticle Preparationmentioning
confidence: 99%
“…The result revealed that the hesperetin and hesperetin-loaded nanoparticles were biocompatible with normal cell line L929 fibroblast cells up to 184.83 and190.88 µg ml -1 for 24 h and up to 133.24 and 134.80 µg ml -1 for 48 h. The antimicrobial activity studies were carried using two different methods against Staphylococcus aureus and Escherichia coli. The MIC (minimal inhibitory concentration) values were 125 µg ml -1 for Escherichia coli and 200 µg ml -1 for Staphylococcus aureus, while the free hesperetin did not demonstrate activity in both strains (MIC value >200 µg ml-1) [111].…”
Section: Antimicrobial Activitymentioning
confidence: 88%
“…advantages, it has been reported that many hydrophobic molecules are loaded into nanoparticular systems, thus increasing their biological activities [15,[27][28][29]. There are many studies on nanoparticular systems in mammalian cell cultures and nanoparticles have been used quite successfully until now in mammalian cell cultures and drug targeting systems [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The Poly-(D,L-lactic-co-glycolic acid) (PLGA) is the most commonly used polymer in the production of polymeric nanoparticles. It has been determined that the systems created by loading the active substances into the PLGA nanoparticle have increased the pharmacokinetic properties, therapeutic indices and biocompatibilities of the active substances compared to the free form [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%